GREN-Wizard: a Tool to Instantiate the GREN Framework - Braga, Rosana T. V.; Masiero, Paulo Cesar (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2002: Anais do XVI Simpósio Brasileiro de Engenharia de Software, 2002)
The GREN-Wizard, a tool to instantiate the GREN framework to particular systems in the business resource management domain, is presented in this paper. It was built based on a pattern language for the same domain, called GRN, which is used during the instantiation process. The GREN-Wizard automatically generates all the code needed to adapt the framework to the particular system, according to the input data supplied by the user. This data consists basically of information about the patterns of GRN applied to model the particular system, together with additional attributes included in the classes that compose each pattern.